Toll‐like receptor 3 activation differentially regulates phagocytosis of bacteria and apoptotic neutrophils by mouse peritoneal macrophages. Issue 1 (18th September 2012) - Deng, Tingting; Feng, Xueying; Liu, Peipei; Yan, Keqin; Chen, Yongmei; Han, Daishu
Abstract : Toll‐like receptor (TLR) activation by microbial pathogens triggers inflammatory responses against microbes. The phagocytic clearance of invading microbes and apoptotic immune cells is essential to resolve inflammation. However, the relationship between TLR activation and phagocytosis is poorly understood. We found that TLR3 activation promotes bacterial uptake through the activation of interferon‐regulating factor 3 (IRF3) and inhibits phagocytosis of apoptotic neutrophils through the activation of nuclear factor‐κB (NF‐κB) by mouse peritoneal macrophages. The TLR signals that regulate the phagocytic ability of macrophages were also induced by TLR4 and TLR5 activation. Further, we demonstrated that TLR‐induced tumor necrosis factor‐α and interferon‐β contributed to the differential phagocytosis of apoptotic neutrophils and bacteria by macrophages. Moreover, activation of IRF3 upregulated the expression of some receptors involved in bacterial uptake, whereas activation of NF‐κB downregulated the expression of molecules that facilitate the phagocytosis of apoptotic cells. These results describe an effect of TLR‐triggered innate immunity on the phagocytic activity of macrophages.